2011
DOI: 10.1007/s00431-011-1507-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of exclusive breastfeeding on the development of children’s cognitive function in the Krakow prospective birth cohort study

Abstract: The main goal of the study was to assess the effect of exclusive breastfeeding on the neurodevelopment of children over a seven-year follow-up period and to test the hypothesis that the observed cognitive gain in breastfed children in the first years of life is a strong predictor of their cognitive development trajectory, which may be continued in later life. The analysis is based on data from the seven-year follow-up of 468 term babies (>36 weeks of gestation) born to non-smoking mothers participating in an o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
81
2
10

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(105 citation statements)
references
References 25 publications
12
81
2
10
Order By: Relevance
“…130 A Krakow prospective birth cohort study revealed that breastfeeding alone positively associates with an increase in IQ of toddlers by 1 year of age and this effect persists through the preschool period. 131 A causal relationship of breastfeeding duration and receptive language and verbal and nonverbal intelligence in school age children (3 and 7 years of age) was established in a U.S. cohort representing 1312 mothers and children. 132 Eight-year-old children who were breastfed for 6 months or more performed better in a general intellectual assessment test.…”
Section: Offspring Cancermentioning
confidence: 99%
“…130 A Krakow prospective birth cohort study revealed that breastfeeding alone positively associates with an increase in IQ of toddlers by 1 year of age and this effect persists through the preschool period. 131 A causal relationship of breastfeeding duration and receptive language and verbal and nonverbal intelligence in school age children (3 and 7 years of age) was established in a U.S. cohort representing 1312 mothers and children. 132 Eight-year-old children who were breastfed for 6 months or more performed better in a general intellectual assessment test.…”
Section: Offspring Cancermentioning
confidence: 99%
“…2 One of good nutrition for an optimal fulfillment is exclusive breastfeeding provided to infants from 0 to 6 months. 5 According to Lind et al, 6 breastfeeding heightens interaction between mother and infant. Breastfeeding improves the mother-and child interaction which is important for cognitive and socio-emotional development of the infants.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 Diversi studi hanno inoltre dimostrato che l'allattamento esclusivo al seno non solo migliora i parametri di crescita, ma favorisce anche un miglior sviluppo neuro-comportamentale. 8 Di rilevanza non trascurabile è infine il ruolo che l'allattamento al seno riveste nel rapporto mamma-neonato, con i conseguenti benefici sullo sviluppo delle competenze genitoriali. Per questi motivi il latte materno è l'alimento raccomandato dall'Organizzazione Mondiale della Sanità (OMS) e dall'UNICEF come forma esclusiva di nutrimento per i primi sei mesi di vita e come costituente fondamentale, opportunamente integrato con altri alimenti, nel periodo del divezzamento.…”
Section: Introduzioneunclassified